Autoignition reactivity of blends of diesel and biodiesel fuels with butanol isomers. Issue 4 (August 2019) - Hernández, Juan J.; Lapuerta, Magín; Cova-Bonillo, Alexis
Abstract: The effect of n-butanol replacement by iso, sec or tert-butanol on the autoignition reactivity of diesel and biodiesel/butanol blends (the total alcohol content being 40% by vol.) was analysed. The study was performed in a constant volume combustion chamber under different initial temperatures (535 °C, ∼600 °C and 650 °C) and n-butanol substitutions. Results show that the effect of the alcohol in both pseudo-binary (diesel fuel/normal, sec, iso or tert-butanol) and pseudo-ternary (diesel fuel/n-butanol/iso, sec or tert-butanol) blends is not that expected from the autoignition properties of the pure isomers. When blended either with diesel or biodiesel fuels, tert-butanol increases the autoignition reactivity of the blend while the other two isomers reduce it. The partial substitution of n-butanol by tert-butanol could be an attractive method for increasing the alcohol content while keeping safe engine operation. Partial substitutions with iso or sec-butanol would promote partially premixed combustion conditions with limited pressure gradient peaks. Chemical kinetics simulations corroborate that the different consumption rates of active radicals from the butanol isomers are responsible for the observed trends. Biodiesel blends are less sensitive to the isomer replacing n-butanol due to its higher number of secondary CH bonds when compared to diesel fuel. Highlights: H-abstraction reactions in diesel/butanol blends are less affected by tBu than by sBu or iBu. Partial substitutions of nBu by tBu allow to increase the renewable fraction without penalizing the combustion phasing. Partial substitutions of nBu by sBu or iBu enable highly premixed combustion with limited pressure gradients. Autoignition of biodiesel is less sensitive to butanol isomers than diesel fuel.